Vibrational circular dichroism of 3-(trifluoroacetyl)-camphor and its interaction with chiral amines - Merten, C.; Jalkanen, Karl; Weiss, V.; Hartwig, A. (Wiley-Liss, 2010)
Vibrational circular dichroism (VCD) spectroscopy and density functional theory (DFT) calculations are used to investigate the keto-enol equilibrium of 3-(trifluoroacetyl)-camphor (TFC) and to study the interaction of TFC with chiral aminesin deuterated Chloroform. It is shown that the VCD spectra of the enol- and keto forms of TFC can clearly be distinguished and that the enol form is favored. By deprotonationof the TFC enol with chiral amines, no indication of a mutual diasteriomeric influenceon the VCD spectra induced by transfer of stereochemical information between the chiralionic species is found, neither experimentally nor theoretically.